A method of simulated motion tracking control based on lyapunov vector field. (April 2020) - Huang, D G; Sun, J; Liu, D
Abstract: For the problem of irregular formation in aircraft cluster planning, this paper proposes a simulated motion tracking control of cluster planning. The simulated motion is the expected motion trajectory for one aircraft provided by the planning system. Using Lyapunov vector field guidance and omnidirectional speed control method, this paper realizes the tracking control of the simulated motion for the aircraft. The simulation results demonstrate that the proposed method can realize the tracking control of the simulated motion and achieve the expected effect, which lays a foundation for the cluster planning.